Instrumentos financieros derivado y los costos de importación - Díaz Salas, Isis Milley (2023)
The constant evolution of the business environment motivates businesses to constantly adapt to changes in order to become more competitive and improve their daily operations. On the other hand, technology importing companies are subject to operational and financial risks, which is why import costs may be affected in the merchandise clearance process, for which it is essential to acquire knowledge of new tools that allow to protect costs and correct errors. For this reason, the objective of this research project is to apply financial derivative instruments such as futures and forwards in technology imports as hedging contracts. The applied methodology was the mixed approach, due to the application of qualitative and quantitative information. The population considered were 4 technology importing companies from the city of Guayaquil in the surveys and the sample was a technology importing company selected in the interview and the collection of financial data. As a result, the lack of knowledge about the benefits of the application of futures and forwards as hedging contracts in technology imports was evidenced, as well as the inconveniences incurred in the merchandise clearance process. In conclusion, an application proposal is proposed that will optimize processes and cover import costs for technology importing companies, for which phases are developed for its correct implementation.